THE NOTION OF SEMANTICS AND LEXICOLOGY (Western European Journal of Linguistics and Education, 2024)
This article deals with exploring the branches of linguistics, namely semantics and lexicology. The prime aim of research implementing detailed information and full notions to these terms. On the top of that, the functions of semantics and lexicology, as well as the role of them are written in article